1993
DOI: 10.1210/jcem.77.1.7686915
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin-like growth factor-binding protein-2 (IGFBP-2) is increased and IGFBP-3 is decreased in patients with prostate cancer: correlation with serum prostate-specific antigen.

Abstract: Insulin-like growth factors (IGFs) are potent mitogens that stimulate the growth of prostate cells. In serum, IGFs circulate bound to IGF-binding proteins (IGFBPs), which modulate their proliferative action. We studied the electrophoretic pattern of IGFBPs in the serum of patients with prostate cancer and in individuals with increased serum levels of prostate-specific antigen (PSA) in the absence of prostate malignancy. Serum IGFBP-2 was dramatically increased in patients with metastatic prostate cancer compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 17 publications
5
83
0
Order By: Relevance
“…Normal and malignant prostate cells produce IGF-1 and several of its binding proteins that can act in a paracrine or autocrine manner (Cohen et al, 1991;Pietrzjowski et al, 1993;Kimura et al, 1996). IGF-binding proteins are found abundantly in prostate secretions, and their serum levels have been reported to differ between patients with and without prostate cancer (Cohen et al, 1993;Kanety et al, 1993). Moreover, prostate cells express IGF-1 receptors and are very sensitive to stimulation by IGFs (Cohen et al, 1991;Kimura et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Normal and malignant prostate cells produce IGF-1 and several of its binding proteins that can act in a paracrine or autocrine manner (Cohen et al, 1991;Pietrzjowski et al, 1993;Kimura et al, 1996). IGF-binding proteins are found abundantly in prostate secretions, and their serum levels have been reported to differ between patients with and without prostate cancer (Cohen et al, 1993;Kanety et al, 1993). Moreover, prostate cells express IGF-1 receptors and are very sensitive to stimulation by IGFs (Cohen et al, 1991;Kimura et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBPs have also been considered in relation to prostate cancer, particularly IGFBP-3 in epidemiological studies Glycemic index in chronic disease LS Augustin et al (Chan et al, 1998;Wolk et al, 1998). Most investigators have reported an inverse association between IGFBP-3 and prostate cancer risk (Chan et al, 1998;Thrasher et al, 1996;Kanety et al, 1993), although others have found no association (Wolk et al, 1998). A possible role of IGFs in prostate carcinogenesis is also suggested by mechanistic studies on Suramin, a drug used in the treatment of advanced prostate cancer, which was shown to suppress IGF-levels (Miglietta et al, 1993;Sartor et al, 1994).…”
Section: Prostate Cancermentioning
confidence: 99%
“…There are several consistent reports that link risk of prostate cancer with high serum levels of IGF-I (Mantzoros et al, 1997;Chan et al, 1998;Wolk et al, 1998;Stattin et al, 2000;Chokkalingam et al, 2001). Decreased levels of IGFBP-3, the most abundant IGFBP in the circulation, have been found in prostate cancer patients and in those with metastatic diseases (Kanety et al, 1993;Chan et al, 1998;Chokkalingam et al, 2001).…”
mentioning
confidence: 99%